From a “great tree” to a new Dawn: race, ethnogenesis, and indigeneity in southern New England - Scott, Mack H., III (Kansas State University, 2019)
The Narragansett leader Miantinomi once explained to European settlers that his people were as a great tree when other tribes in the region were mere twigs. But in the years, decades, and centuries that followed the proclamation the authority and dominion claimed by Indians was reduced significantly, and the Narragansetts were left searching for a new dawn in which the continuation and relevancy of their community might be affirmed. This study traces the historical persistence of the Narragansetts by exploring how the Indians, at times, shifted the composition of their community in a process scholars refer to as ethnogenesis—the repeated reforming and reshaping of Native societies. This work shows that how the Narragansetts conceptualized and expressed evolutions within their community sometimes conflicted with the definitions and expectations of their non-indigenous neighbors, thus, creating interpretive conflicts that, in time, inspired challenges to the authenticity of the Narragansetts. Finally, this work examines how the dictates of others—whether the Indians sought to comply or not—eventually informed how many Narragansetts understood and professed their distinctive yet evolving identity as indigenous persons. According to an interpretation that remained unchallenged for close to three centuries, on 19 December 1676, the Narragansetts suffered a debilitating defeat when a regiment under the direction of the United Colonies—a military alliance comprised of soldiers from Connecticut, Massachusetts, and Plymouth—marched into southern Rhode Island and valiantly subdued what had been a belligerent and bellicose tribe. The demographic, social, political, cultural, and economic consequences of the loss left the Narragansetts reeling until 1880 when state officials finally and compassionately detribalized the Narragansetts. Although this false narrative explaining the supposed demise of southern New England’s principal indigenous community was specific, it was not unique. Accounts proclaiming the disappearance of Native peoples were used to affirm Euro-American claims to land throughout North America. When coupled with what Jean O’Brien has termed replacement narratives—chronicles designed to diminish the historical significance of Indian communities—accounts proclaiming the seemingly natural demise of Indigenous peoples have enabled English colonists and later American citizens to reap the rewards of a landscape seemingly devoid of indigenous persons while avoiding the territorial, legal, and ethical complications their presence and persistence would have created. Despite the preponderance of evidence found in more recent scholarship which lays bare the fallacies associated with what Phillip Deloria has referred to as the myth of the vanishing Indian, the falsehoods purporting the demise and disappearance of the Narragansetts remain mostly intractable in local lore. This may be due to the fact that public recognition of the continued existence of Rhode Island’s once-vibrant indigenous population portends tremendous economic and territorial consequence for a state comprised entirely of land originally claimed by the Narragansetts. Within this context, it is not difficult to understand why some Rhode Islanders remain reluctant to acknowledge the persistence of the Narragansetts as a community. Instead—as non-Indians in the region have done for hundreds of years—many contemporary Rhode Islanders continue to challenge the racial, cultural, and historical authenticity of those who purport to be descended from the great tree.
Keywords: Rhode Island; Narragansett; Ethnogenesis